Analisis Faktor Penyebab Kerusakan Berkas Rekam Medis di Rumah Sakit Universitas Airlangga - Aulia Nurul Kholifah; Novita Nuraini; Andri Permana Wicaksono (Politeknik Negeri Jember, 2020)
Medical records are files that contain records and documents regarding patient identity, examination results,treatment, actions and other services that have been provided to patients. Management of medical records is oneof medical support services. Based on the results of a preliminary study conducted at Airlangga UniversityHospital Surabaya it is known that in February 2020 amount 104 files were damaged so that the forms containedin them could be torn. This research was aimed to analyze the factors that cause damage to medical record filesat Airlangga University Hospital Surabaya. This type of research uses qualitative and data collection withinterviews and observations by using the analysis of 5M management elements is Man, Machine, Method,Material, Money. The population in this study is the medical records officer filing room section of 5 officers. Theresults obtained are that there are still many medical records officers who have a background not DIII medicalrecords, the lack of socialization of SOPs related to the maintenance of medical record files, limited number ofrack filing, and the less used folder material. So the suggestion made by the researchers is to redesign themedical record file folder by using a color code, and calculate the rack filing needs.